Systematic review on the treatment of isolated local recurrence of pancreatic cancer after surgery; re-resection, chemoradiotherapy and SBRT. Issue 2 (February 2017) - Groot, Vincent P.; van Santvoort, Hjalmar C.; Rombouts, Steffi J.E.; Hagendoorn, Jeroen; Borel Rinkes, Inne H.M.; van Vulpen, Marco; Herman, Joseph M.; Wolfgang, Christopher L.; Besselink, Marc G.; Molenaar, I. Quintus
Abstract: Background: The majority of patients who have undergone a pancreatic resection for pancreatic cancer develop disease recurrence within two years. In around 30% of these patients, isolated local recurrence (ILR) is found. The aim of this study was to systematically review treatment options for this subgroup of patients. Methods: A systematic search was performed in PubMed, Embase and the Cochrane Library. Studies reporting on the treatment of ILR after initial curative-intent resection of primary pancreatic cancer were included. Primary endpoints were morbidity, mortality and survival after ILR treatment. Results: After screening 1152 studies, 18 studies reporting on 313 patients undergoing treatment for ILR were included. Treatment options for ILR included surgical re-resection (8 studies, 100 patients), chemoradiotherapy (7 studies, 153 patients) and stereotactic body radiation therapy (SBRT) (4 studies, 60 patients). Morbidity and mortality were reported for re-resection (29% and 1%, respectively), chemoradiotherapy (54% and 0%) and SBRT (3% and 1%). Most patients had a prolonged disease-free interval before recurrence. Median survival after treatment of ILR of up to 32, 19 and 16 months was reported for re-resection, chemoradiotherapy and SBRT, respectively. Conclusion: In selected patients, treatment of ILR following pancreatic resection for pancreatic cancer seems safe, feasible and associated with relatively good survival.